PENGARUH BUTEYKO BREATHING EXERCISE TERHADAP PENINGKATAN ARUS PUNCAK EKSPIRASI PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA III - Bowo Laksono, Abdurrahman Berbudi; Sariana, Erna; Ramadoni, Ramadoni (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background: Aging is the cause of widespread progressive changes in all aspects of biology that result in susceptibility to various diseases. The changes seen in the decrease in peak expiratory flow due to age often cause less air to enter the body. A decrease in peak expiratory flow will result in hypoxemia and hypercapnia which will lead to respiratory failure.. Buteyko Breathing Exercise is an intervention that supports increasing peak expiratory flow so that it can open the breathing path. Objective: Knowing the Effect of Buteyko Breathing Exercise on Increasing Peak Expiratory Flow in the Elderly. Method: This study uses the type of experimental research with one group pretest - posttest which is carried out at the Tresna Budi Mulia III Social Institution. In this study using 13 respondents who were selected using the Random Sampling Technique. Measurement of Peak Expiratory Flow using a Peak Flow Meter on baseline and final data after intervention for 4 weeks with a frequency of 2 times a week. Results: Changes in the increase in peak expiratory flow before and after the intervention obtained a value of p = 0.000 (p < 0.05). Conclusion: There is an effect of Buteyko Breathing Exercise on Increasing Peak Expiratory Flow in the Elderly at Tresna Werdha Budi Mulia III Social Home.